Поверхностныe электроупругие волны лява в слоистой системе с пьезоэлектрической подложкой и мягким диэлектрическим слоем ( Исследование характеристического уравнения. – Часть I) - З. Н. Даноян; Н. З. Даноян; Г. А. Манукян (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the article is investigated the existence and the behaviour Love’s surface electroelastic waves in a layered system with a piezoelectric substructure if the class 6,4, 6mm, 4mm, 622, 422 and a soft dielectric isotropic layer with a finite arbitrary thichness depending on the physicomechanical properties of the system and the reative thichness of the layer. The characteristic equation at the surface wave is investigated in the case of the soft layer when the propagation velocity of volume of clastic waves in the layer is less than the propagation velocity of the volume electroelastic waves in the substracture. In particular it is shown that the existence of split waves of Love’s type due to solely piezoelectrical effect.
Keywords: Mechanics of deformable solids; Generalities, axiomatics, foundations of continuum mechanics of solids; Waves